Extraction Flavonoids of Beluntas Leaves (Pluchea indica L.) Using Maceration Method with Fermentation - Putri Dwi Rahayu; Suprihatin; Sani; Imanda, Arsyi (Prodi Kimia, 2024)
Pluchea Indica L. or beluntas plant is a medicinal plant that contains several bioactive components including tannins, alkaloids, flavonoids, saponins and essential oils. The flavonoids in beluntas leaves can act as antioxidant, anticancer and antidiabetic compounds. This research aims to determine the effect of fermentation time and maceration time and to obtain the best conditions for the flavonoid levels of beluntas leaf extract. One way to obtain high amounts of beluntas leaf flavonoids is by maceration extraction with fermentation of Rhizopus sp. This research was carried out by fermenting beluntas leaf powder using Rhizopus sp at a temperature of 30°C and aerobic conditions with a time of (48; 72; 96; 120; 144) hours. After fermentation, the beluntas leaf powder will be analyzed using UV-Vis spectrophotometry. Next, the beluntas leaf powder will be extracted using the maceration method using 90% methanol solvent with a maceration time (24; 36; 48; 60; 72) hours, then filtered to separate the filtrate and sediment. The filtrate was distilled to obtain beluntas leaf extract, then the beluntas leaf extract was analyzed for flavonoid levels using the UV-Vis Spectrophotometry method. The results showed that fermentation time and maceration extraction time had an effect on the flavonoid content of beluntas leaf extract. The best flavonoid content was obtained at 1.0398% at a fermentation time of 96 hours and a maceration time of 48 hours.